Gender Deviations Analysis in the Danish Girl - Winda Rizky Nurdiyanti; Zumrotul Muniroh (JEdu: Journal of English Education, 2022)
The purpose of this study is to identify and analyze gender deviations shown in the film The Danish Girl. The theory used in analyzing gender deviation is Sigmund Freud's Psychoanalytic theory which includes the id, ego and superego. The research method used is qualitative. As for the research technique using library techniques that focus on books as a supporter of the theory in this study. The results of the analysis show that there are 9 data points for id attitudes with a percentage of 33.1%, 19 data for ego attitudes with a percentage of 63.3%, and 2 data for superego with a percentage of 6.7%. So, it can be concluded that the most dominant deviant attitude is the ego attitude.